Method for improving stability of electroreduction CO2 slurry and method for preparing electrode by using slurry

By introducing nanocarbon materials in the electrocatalytic carbon dioxide process and optimizing the slurry dispersion process, the problem of poor stability of the cathode copper-based catalyst slurry is solved, significantly improving the stability and electrochemical performance of the electrode, and extending the lifetime of the electrocatalytic reaction.

CN119530852APending Publication Date: 2025-02-28SHENZHEN INST OF ADVANCED TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411773482.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, the stability of the cathode copper-based catalyst slurry during electrocatalytic carbon dioxide is poor, resulting in peeling of electrode materials and loss of active substances, affecting the multi-carbon production effect of the electrocatalytic reactor.

Method used

By introducing nanocarbon materials as conductive particles and using a composite dispersion process of two segmented ball mills + ultrasound, the slurry dispersion process conditions are optimized and the stability of the slurry is improved. Specific steps include mixing drying, grinding, ball milling and sonication to form a stable multidimensional network structure that inhibits slurry stratification and settlement.

Benefits of technology

The stability and storage time of the cathode copper-based catalyst slurry is significantly improved, the rapid settlement and layering of the slurry is avoided, the uniformity and electrochemical performance of the electrode are improved, and the lifetime of the electrocatalytic reaction is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

According to the method for improving the stability of the electroreduction CO2 slurry and the method for preparing the electrode by adopting the slurry, the stability of the slurry is remarkably improved by introducing a specific additive and optimizing slurry dispersion process conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a method for improving the electroreduction of CO 2 The invention relates to a method for improving the stability of a slurry and a method for preparing an electrode using the slurry. Background Art

[0002] Carbon dioxide electrocatalysis is a method that uses electrocatalysts to convert carbon dioxide into useful chemicals. With the increasing global demand for sustainable energy and carbon emission reduction, carbon dioxide electrocatalysis has become one of the research hotspots. This technology can achieve efficient conversion of carbon dioxide through electrochemical reactions and has potential applications such as reducing greenhouse gas emissions, resource utilization and energy storage.

[0003] There are great challenges in the industrial application of carbon dioxide electrocatalytic technology, especially the core electrode materials of electrocatalytic reactors cannot be used stably for a long time, have short life, poor stability and low efficiency, resulting in high cost of current industrial electrocatalytic technology and difficulty in large-scale industrial promotion. Among them, the stability of the catalyst slurry coated on the electrode material is an important problem that restricts the large-scale industrial promotion of electrode materials. Existing studies have shown that the stability of the slurry directly affects many aspects such as the catalytic activity, cycle life, and energy efficiency of the electrode surface. Catalyst slurry refers to the liquid suspension containing electrocatalysts used in electrocatalytic reactions. Since electrocatalysts often exist at nano or submicron scales and need to interact with the electrolyte solution and carbon dioxide solution in the reactor, the electrocatalyst is dispersed in the solution to form a slurry and coated on the corresponding substrate material to form an electrode, which can increase the contact area between the catalyst and the reactant, thereby improving the reaction efficiency. The main problems that need to be solved in the application of catalyst slurry are dispersibility and stability. Among them, the stability of the slurry refers to the long-term stability and anti-deposition ability of the electrocatalyst in the slurry, which is mainly manifested in the peeling of the electrode material and the loss of active substances, thereby reflecting the good or bad dispersion. During the slurry preparation process, solid particles such as catalysts may aggregate, precipitate or deposit, resulting in loss of catalytic activity. In addition, other components in the slurry, such as electrolytes and reaction products, may also interact with the electrocatalyst and affect its stability. Solving the problem of catalyst slurry stability can ensure the long-term service life and high-efficiency performance of the electrocatalyst.

[0004] At present, there are many studies on improving the stability of catalyst slurries related to combustion batteries or water electrolysis for hydrogen production, but there are few studies on the stability of electrocatalytic carbon dioxide catalyst slurries. The common means to solve the stability of catalyst slurries is to use ultrasound or ball milling, but there are problems such as uneven mixing, poor dispersion, too fast sedimentation, and bubbles that do not disappear. As described in patent CN202311030573, the addition of conductive particles improves the stability of combustion batteries, but the dispersion of slurry solids and the bubble problems in the slurry preparation process are all involved. As described in patent CN11 6826071A, the addition of conductive particles improves the stability of combustion batteries. This method describes the proportion of conductive particles and the dispersion method in detail, and the applicability to electrocatalytic carbon dioxide is unknown. As described in CN201711397976.7, this method only describes the way different reagents are added, and the impact of the slurry dispersion step on its stability is not described in detail.

[0005] The stability of the catalyst slurry used in the electrocatalytic carbon dioxide production process, especially the cathode copper-based catalyst slurry, needs to be further improved to achieve its industrial application. During the preparation of the cathode electrode, the slurry sedimentation rate is too fast, resulting in uneven loading of metal particles in the catalyst layer during electrode coating, further leading to poor electrode uniformity, which greatly affects the effect of the electrocatalytic reactor in producing multi-carbon products. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention proposes a new preparation method for improving the stability of cathode copper-based catalyst slurry for electrocatalytic reduction of carbon dioxide to produce polycarbon. The stability of the slurry is significantly improved by introducing specific additives and optimizing the slurry dispersion process conditions.

[0007] Based on this, the present invention provides a preparation method for improving the stability of electrocatalytic reduction of carbon dioxide slurry, which comprises:

[0008] In the first step, the solid powdered catalyst and the conductive particles are weighed, mixed, and dried in an oven;

[0009] The second step is to grind the mixture obtained in the first step into a powder mortar to ensure that the solid particles are uniform in size before preparing the slurry, and then sieve it through a 400-mesh screen;

[0010] The third step is to prepare the slurry and adopt a composite dispersion process of two-stage ball milling + ultrasound.

[0011] In the first step, the conductive particles are nanocarbon materials, preferably one or more combinations of Ketjen black, carbon nanotubes, and graphene, more preferably a mixture of Ketjen black and graphene, and the mass ratio of Ketjen black to graphene is preferably 1-2:1-2, more preferably 1:1.

[0012] The third step is further specifically as follows: the copper-based catalyst, Ketjen black and graphene ground in the second step, isopropyl alcohol and ultrapure water are mixed according to a certain ratio, placed in a zirconia ball mill, ball-milled once, and after taking out the slurry, a binder and microcrystalline cellulose are added, and ball-milled twice. After completion, the slurry is taken out and placed in an ultrasonic instrument for ultrasonication and vibration to remove bubbles.

[0013] The present invention also provides a method for preparing an electrode using the slurry, which comprises:

[0014] The prepared slurry is coated on carbon paper through a vacuum heating wire rod scraper coating device, and high temperature resistant tape is pasted around the carbon paper to prevent the slurry from overflowing from the four sides to the back of the base material. It is vacuum adsorbed on the heating panel of the coater, and the scraper is fixed on one end of the carbon paper. The mixed slurry is placed close to the bottom of the scraper. The coating thickness is set to 100μm-120μm, the coating heating plate temperature is 25-80℃, and the scraper coating speed is 1-10mm / s.

[0015] Beneficial effects of the present invention

[0016] The present invention proposes a new preparation method for improving the stability of cathode copper-based catalyst slurry for electrocatalytic reduction of carbon dioxide to produce polycarbon, and significantly improves the stability of the slurry by introducing specific additives and optimizing the slurry dispersion process conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Comparison of the change of sedimentation of the slurry of Example 1 of the present invention and the slurry of Comparative Example 1 over time;

[0018] Figure 2a This is the zate potential diagram of the slurry of Comparative Example 1 of the present invention;

[0019] Figure 2b This is the zate potential diagram of the slurry in Example 1 of the present invention;

[0020] Figure 3a This is the light intensity distribution diagram of the particle size of the first ball milling slurry;

[0021] Figure 3b Correlation curve of particle size distribution of primary ball mill slurry;

[0022] Figure 4a This is the light intensity distribution diagram of the particle size of the slurry after two segmented ball millings;

[0023] Figure 4b Correlation curve of particle size distribution of slurry after two stage ball milling. DETAILED DESCRIPTION

[0024] The present invention provides a preparation method for improving the stability of electrocatalytic reduction of carbon dioxide slurry, which comprises:

[0025] In the first step, the solid powdered catalyst and the conductive particles are weighed, mixed, and dried in an oven;

[0026] The second step is to grind the mixture obtained in the first step into a powder mortar to ensure that the solid particles are uniform in size before preparing the slurry, and then sieve it through a 400-mesh screen;

[0027] The third step is to prepare the slurry and adopt a composite dispersion process of two-stage ball milling + ultrasound.

[0028] In the first step, the conductive particles are nanocarbon materials, preferably one or more combinations of Ketjen black, carbon nanotubes, and graphene, more preferably a mixture of Ketjen black and graphene, and the mass ratio of Ketjen black to graphene is preferably 1-2:1-2, more preferably 1:1.

[0029] By doping conductive particles in the catalyst slurry, the mutual repulsion between catalyst particles in the slurry is increased, the slurry stratification is inhibited, the rapid sedimentation of the slurry is avoided, and the stability and storage time of the slurry are improved. By selecting Ketjen black and graphene for mixing, the unique branched Ketjen black and the small flake graphene form a suitable force. The graphene can be filled between the catalysts and the combination with the unique branched Ketjen black can form a multi-dimensional network structure in the slurry to inhibit the slurry stratification. The cathode copper-based catalyst used in the electrocatalytic carbon dioxide is a transition metal oxide. The addition of graphene to form a composite material is helpful to solve the problems of volume expansion and short life. The addition of graphene can limit the particle growth of transition metal oxides during the electrochemical reaction, maintain a smaller particle size, and thus reduce volume expansion. The two-dimensional layered structure of graphene can provide more contact points and a larger contact area for transition metal oxides, which helps to improve the structural stability of the electrode. Extend the reaction life of electrocatalytic carbon dioxide.

[0030] The third step is further specifically as follows: the copper-based catalyst, Ketjen black and graphene ground in the second step, as well as isopropyl alcohol and ultrapure water are weighed according to a ratio, placed in a zirconia ball mill, ball milled for 12 hours, and after taking out the slurry, 10wt% binder of Versogen PiperION A5 and microcrystalline cellulose are added, and ball milled for a second time for 12 hours. After completion, the slurry is taken out and placed in an ultrasonic instrument for 5 minutes to remove bubbles by shaking.

[0031] The present invention adopts a two-stage ball milling method. Before the slurry binder is added, the other ingredients are wet-milled in a planetary ball mill, with the purpose of breaking up large agglomerates of solid particles except the binder, further improving the dispersion of the solid particles in the slurry, adding the binder and ball milling again to fully fuse the binder and solid particles, thereby improving the viscosity and stability of the slurry.

[0032] In the present invention, in order to make the slurry more stable, microcrystalline cellulose is added in the first step to form a three-dimensional network structure. Microcrystalline cellulose can absorb water and swell in water to form a three-dimensional network structure. This structure helps to stabilize the active substances in the slurry and reduce sedimentation and aggregation. Increase viscosity. The addition of microcrystalline cellulose increases the viscosity of the slurry, thereby improving the anti-rheological properties of the slurry and helping to maintain the uniformity of the coating during the coating process. Provide a physical barrier. The particles of microcrystalline cellulose can act as a physical barrier to prevent direct contact between active material particles and reduce aggregation between particles. The dispersion between the copper-based catalyst for carbon dioxide electroreduction and the solid particles of the carbon material is increased to avoid the sedimentation of the solid particles of the slurry, thereby further improving the viscosity and stability of the slurry.

[0033] The present invention also provides a method for preparing an electrode using the slurry, which comprises:

[0034] The prepared slurry is coated on carbon paper (carbon paper brand model: JNTG A20L) by vacuum heating wire rod blade coating equipment, the carbon paper is cut into 8×12 cm, and 0.025 mm high temperature resistant tape is pasted around to prevent the slurry from overflowing from the four sides to the back of the base material, and vacuum adsorbed on the heating panel of the coater, the blade is fixed on one end of the carbon paper, and the mixed slurry is placed close to the bottom of the blade. The coating thickness is set to 100 μm-120 μm, the heating plate temperature is 25-80°C, and the blade coating speed is 1-10 mm / s. The optimal coating parameters are: carbon paper model JNTG A20L, coating speed 2 mm / s, coating thickness 120 μm, and coating heating plate temperature 40°C.

[0035] The following will be combined with the embodiments of the present invention and the accompanying drawings to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] The proportions of the slurry components are shown in Table 1.

[0038] Table 1 Slurry composition ratio

[0039] Element content CuO (<50 nm particle size (TEM), Sigma-Aldrich) 2021mg Ketjen Black + Graphene (mass ratio 1:1) 379mg Versogen PiperION A5 10wt% Binder 4800mg Isopropyl alcohol 1200mg Deionized water 1200mg

[0040] The slurry ratio has a solid content of about 30% and an I / C of about 24%, wherein I / C represents the mass percentage of the solid polymer in the binder to the mass percentage of the catalyst.

[0041] According to the ratio in the table above, the copper-based catalyst, Ketjen black and graphene were weighed and ground in a mortar, passed through a 400-mesh sieve, and a planetary ball mill (Michi Planetary Ball Mill-YXQM-0.4L) was used. A 25mL zirconia ball mill and base were prepared by the manufacturer. The specifications of the zirconia ball mill beads were 10 / 8 / 5mm. The 25mL ball mill was placed with 1 / 3 / 12 large, medium and small ball mill beads. The ground copper-based catalyst, Ketjen black and graphene, as well as isopropanol and ultrapure water, were weighed and placed in a 25mL zirconia ball mill according to the ratio. The ground copper-based catalyst, Ketjen black and graphene, as well as isopropanol and ultrapure water, were weighed and placed in a 25mL zirconia ball mill. The ball mill was milled for 12 hours at a time. After the slurry was taken out, 4800mg of 10wt% binder of Versogen PiperION A5 and 24mg of microcrystalline cellulose were added. The ball mill was milled for 12 hours. The slurry was taken out and placed in an ultrasonic machine. The frequency range was 500MHz, and the ultrasonic was performed for 5 minutes. Degassing treatment, ice bath, and ultrasonic treatment were performed for 5 minutes.

[0042] In order to avoid the influence of air humidity on reagents, all powdered reagents used in the experiment were heated and dried in an oven at 60°C before slurry preparation.

[0043] Comparative Example 1

[0044] The preparation method is the same as that in Example 1, except that Ketjen black + graphene is not added.

[0045] pass Figure 1 It can be seen from the comparison that the solid sedimentation of the slurry without adding nano-carbon conductive particles is obvious in a short time, and the solid-liquid separation is basically achieved in 24 hours, while the slurry of Example 1 with added conductive particles is still evenly distributed after 120 hours. Figure 2a and Figure 2b It can be seen from the comparison that the average Zeta potential (mV) of the slurry after adding conductive particles is: -13.85, which is less than -27.12 without adding conductive particles.

[0046] Comparative Example 2

[0047] Compared with Example 1, the difference lies in that Ketjen black + carbon nanotubes are used.

[0048] Comparative Example 3

[0049] Compared with Example 1, the difference lies in that carbon nanotubes + graphene are used.

[0050] The types of conductive particles include conductive polymers and carbon materials. Currently, the conductive particles commonly used in the field of electrochemical slurries are mainly nano-carbon materials, including: carbon black, graphite, acetylene black, carbon nanotubes, graphene, carbon nanotubes, etc. The type, amount, and ratio of carbon materials affect the stability of the slurry. However, different carbon materials have their own unique properties and limitations. For example, carbon nanotubes are one-dimensional structures. They are usually clustered and oriented during preparation. Mechanical external force is required to disperse them evenly. In the dry state, the dispersed carbon nanotubes will still agglomerate into a ball shape. Therefore, the selection of conductive particles suitable for the electroreduction of carbon dioxide is crucial.

[0051] The present invention is tested by taking advantage of the spatial structure of various conductive particles, preferably Ketjen black, carbon nanotubes and graphene, and the parameter comparison is shown in Table 2.

[0052] Table 2 Comparison of nanomaterial parameters

[0053] Material shape Size(nm) <![CDATA[Specific surface area (m 2 / g)]]> Resistivity(Ω-cm) Ketchen Black Branch Chain 30-40 800-1400 <![CDATA[6.1*10 -2 ]]> Carbon Nanotubes Hollow Fiber 5-40 100-400 <![CDATA[3.5*10 -2 ]]> Graphene Flake 0.016 60-300 9.2

[0054] Ketjen black has a unique structure and a super high specific surface area, and the pole piece can better adsorb and retain the slurry; carbon nanotubes can cover the copper-based catalyst for the electroreduction of carbon dioxide and fill the particles with excellent performance; graphene fills more between catalysts, each with its own characteristics. The present invention further compares the electrochemical impedance of the slurry with different types and components of conductive particles added by comparing the mixed use of different conductive materials, by achieving a solid content of conductive particles accounting for 10% of the solid content of the catalyst, and keeping other conditions consistent. The results are shown in Table 3.

[0055] Table 3 Effect of conductive particle composition ratio on electrochemical impedance

[0056] name Component ratio Electrochemical impedance (Ω) Ketchen Black / 87.5 Carbon Nanotubes / 50.1 Graphene / 28.2 Ketjen Black + Carbon Nanotubes 1:1 43.2 Ketjen Black + Graphene 1:1 35.7 Carbon nanotubes + graphene 1:1 25.7

[0057] Ketjen black plays a very important role in the preparation of stable slurry electrodes. It can not only serve as a self-healing current collector, but also prevent large particles of active materials from sinking through its hyperbranched structure to maintain the stability of the suspension. The combination of Ketjen black + graphene was selected after comprehensive consideration. The unique branched Ketjen black and the small flake graphene form a suitable force, and the graphene can be filled between the catalysts. This avoids the formation of large particles caused by strong intermolecular forces between Ketjen black particles. The combination of Ketjen black + graphene gives full play to the respective advantages of Ketjen black and graphene, and can form a multi-dimensional network structure in the slurry to inhibit the slurry from stratifying and avoid the rapid sedimentation of the slurry. In addition, the copper-based catalyst used for electrocatalysis of carbon dioxide is a transition metal oxide, and the transition metal oxide has a high gram capacity. The addition of graphene to form a composite material is helpful to solve the problems of volume expansion and poor circulation. It can be seen from Table 2 that the combination of Ketjen black + graphene has a lower EIS ohm value than each of them added separately.

[0058] Comparative Example 4

[0059] Various ingredients were weighed according to the proportions in Example 1, 24 mg of microcrystalline cellulose was added, and the mixture was placed in a 25 mL zirconium oxide ball mill jar and ball milled for 24 h. After the slurry was taken out, it was placed in an ultrasonic instrument and ultrasonicated for 5 min.

[0060] Comparative Example 4 (single ball milling): The stability is slightly poor. Although no obvious stratification occurs after one week, the solid particles settle seriously. Example 1 (twice segmented ball milling): The mixed slurry adopts two segmented ball milling. After one week, the solid precipitation is lighter than that of the single ball milling. The slurry mixed in two ways is coated on JNTG A20L. The electrode coated under the same conditions also shows that the electrode surface load prepared in Example 1 (twice segmented ball milling) is more uniform, and the average resistivity is lower by 18.67mΩ·cm. The main reason is that wet grinding before adding the slurry binder can break the large agglomerates of solid particles other than the binder, further improving the dispersion of solid particles in the slurry. Add the binder and ball mill again to fully fuse the binder and solid particles to improve the dispersibility and stability of the slurry. Finally, the slurry is taken out of the ball mill and placed in an ultrasonic machine, and degassing is carried out at 500kHz ultrasound for 5min. The ultrasonic degassing time should not be too long. Excessive power and long time may break the binder molecular chain and weaken the bonding effect. Due to long-term high-speed wet grinding in a ball mill, the experiment found that a large number of dense bubbles appeared in the slurry. Simple ultrasound can alleviate the problem but cannot solve it. Therefore, we increased the static time of the slurry. The static time was too long and the slurry sedimentation problem occurred. The addition of 24 mg of microcrystalline cellulose made the slurry more viscous, increased the dispersion between the copper-based catalyst for carbon dioxide electroreduction and the solid particles of carbon materials, avoided the sedimentation of the slurry, and further improved the viscosity and stability of the slurry.

[0061] Table 5: Comparison of results of different ball milling methods

[0062]

[0063] The electrode is formed in one step by coating method. The instrument used is a vacuum heating wire rod scraper coating machine. The carbon paper is JNTG A20L. The carbon paper is placed in an oven at 60°C for 30 minutes for drying before coating. The carbon paper is cut into 8×12cm and vacuum adsorbed on the heating panel of the coating machine. The heating temperature is 60°C, the coating thickness is 150μm, and the coating speed is 2mm / s. Under the same conditions, the electrode load coated on JNTG A20L is more uniform, and the average resistivity of 18.67mΩ·cm obtained by the test is relatively smaller, and the electrochemical performance of the electrode is better. Based on the above results, JNTG A20L is preferred as the carbon paper.

[0064] In order to further verify the dispersibility of the slurry, the following tests were performed on Example 1 and Comparative Example 4. The results are shown in Table 6. Figure 3a , Figure 3b and Table 7, Figure 4a and Figure 4b .

[0065] Table 6 Test results of the first ball milling scheme of Comparative Example 4

[0066] name average value Minimum Maximum Z-mean(nm) 595.2 595.2 595.2 Polydispersity Index (PI) 0.6084 0.6084 0.6084 Mean value of peak 1 of particle size intensity distribution sorted by area (nm) 525.3 525.3 525.3 Area of ​​peak 1 of particle size intensity distribution sorted by area (%) 83.15 83.15 83.15 Mean value of peak 1 of particle size intensity distribution sorted by area (nm) 165.8 165.8 165.8 Area of ​​peak 1 of particle size intensity distribution sorted by area (%) 16.85 16.85 16.85

[0067] Table 7 Test results of the secondary ball milling scheme of Example 1

[0068] name average value Minimum Maximum Z-mean(nm) 297.4 297.4 297.4 Polydispersity Index (PI) 0.1695 0.1695 0.1695 Mean value of peak 1 of particle size intensity distribution sorted by area (nm) 325.6 325.6 325.6 Area of ​​peak 1 of particle size intensity distribution sorted by area (%) 100 100 100

[0069] It can be seen from Tables 6 and 7 above that the slurry after two ball millings is more evenly dispersed with an average particle size of 297.4 nm; the average particle size after one ball milling is 595.2 nm, and the appearance of a double peak phenomenon indicates that there is uneven size of particles in the slurry and poor dispersion.

[0070] Optimization of coating experiment parameters - coating speed

[0071] The slurry adopts the slurry ratio of Example 1, and the dispersion method is two-stage ball milling. 24 mg of microcrystalline cellulose is added in the second stage of ball milling. The electrode is formed in one step by coating method. The instrument used is a vacuum heating wire rod scraper coating machine. The carbon paper is JNTG A20L. Before coating, the carbon paper is placed in an oven at 60°C for 30 minutes for drying. The carbon paper is cut into 8×12cm and vacuum adsorbed on the heating panel of the coating machine. The heating temperature is 25°C, the coating thickness is 150μm, and the coating speed is shown in Table 8.

[0072] Table 8 Coating speed

[0073]

[0074]

[0075] The appropriate coating speed can ensure the uniform distribution of the slurry on the substrate, making the average resistivity of the electrode itself smaller and the conductive performance of the electrode better. The coating speeds are set to 1, 2, 5, and 10 mm / s respectively. If the speed is too fast, the coating will be uneven, with stripes or ripples; if the speed is too slow, the coating may be too thick and unevenly dried. As can be seen from the table above, when the coating speed is 2 mm / s, the average resistivity of the electrode is the minimum of 18.67 mΩ·cm, and the slurry is more evenly distributed on the carbon paper.

[0076] Optimization of coating experiment parameters - coating heating plate temperature

[0077] 25℃-80℃ (the rest of the operation process and parameters are consistent with Table 8, and the coating speed is preferably the optimal 2mm / s in Table 8)

[0078] Table 9 Coating heating plate

[0079] Experiment No. Experiment 5 Experiment 6 Experiment 7 Experiment 8 Coating speed (mm / s) 2 2 2 2 Coating thickness (μm) 120 120 120 120 Coating heating plate temperature (℃) 25 40 60 80 Average resistivity (mΩ·cm) 22.3 15.95 19.54 20.48 Carbon paper JNTG A20L JNTG A20L JNTG A20L JNTG A20L

[0080] The appropriate drying temperature helps the catalyst coating to form a uniform surface during the leveling process. The coating heating plate temperatures were set to 25, 40, 60, and 80°C, respectively. The difference may be caused by the fact that if the drying temperature is too low, the solvent in the electrode may not be completely evaporated, resulting in the electrode not being completely dried; the uneven coating or cracking caused by excessive temperature may also cause changes in the structure of the electrode material, and the binder and conductive additives added to the slurry migrate to the surface of the electrode, affecting the electrochemical properties of the electrode. As can be seen from the table above, when the coating speed is 40°C, the average resistivity of the electrode is a minimum of 15.59mΩ·cm, and the slurry is more evenly distributed on the carbon paper.

[0081] The best coating parameters were as follows: carbon paper (GDL) model JNTG A20L, coating speed 2 mm / s, coating thickness 120 μm, and coating heating plate temperature 40 °C.

[0082] For any technician familiar with the field, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or to modify it into an equivalent embodiment with equivalent changes.

[0083] Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A preparation method for improving the stability of electrocatalytic reduction of carbon dioxide slurry, characterized in that: include: In the first step, the solid powdered catalyst and the conductive particles are weighed, mixed, and dried in an oven; The second step is to grind the mixture obtained in the first step into a powder mortar to ensure that the solid particles are uniform in size before preparing the slurry, and then sieve it through a 400-mesh screen; The third step is to prepare the slurry and adopt a composite dispersion process of two-stage ball milling + ultrasound.

2. The method for improving the stability of electrocatalytic reduction of carbon dioxide slurry according to claim 1, characterized in that: In the first step, the conductive particles are nano-carbon materials.

3. The method for improving the stability of electrocatalytic reduction of carbon dioxide slurry according to claim 2, characterized in that: The nano carbon material is one or a combination of Ketjen black, carbon nanotubes and graphene.

4. The method for improving the stability of electrocatalytic reduction of carbon dioxide slurry according to claim 3, characterized in that: The nano carbon material is a mixture of Ketjen black and graphene, and the mass ratio of Ketjen black to graphene is 1-2:1-2.

5. The method for improving the stability of electrocatalytic reduction of carbon dioxide slurry according to claim 1 or 2, characterized in that: The third step is further specifically as follows: the copper-based catalyst, Ketjen black and graphene ground in the second step, isopropyl alcohol and ultrapure water are mixed according to a certain ratio, placed in a zirconia ball mill, ball-milled once, and after taking out the slurry, a binder and microcrystalline cellulose are added, and ball-milled twice. After completion, the slurry is taken out and placed in an ultrasonic instrument for ultrasonication and vibration to remove bubbles.

6. A method for preparing an electrode using the slurry according to any one of claims 1 to 5, characterized in that: include: The prepared slurry is coated on the carbon paper through the vacuum heating wire rod scraper coating equipment, and high temperature resistant tape is pasted around the carbon paper to prevent the slurry from overflowing from the four sides to the back of the base material. It is vacuum adsorbed on the heating panel of the coating machine, and the scraper is fixed on one end of the carbon paper. The mixed slurry is placed close to the bottom of the scraper, and the coating thickness is set for scraping.

7. The method for preparing an electrode from a slurry as claimed in claim 6, characterized in that: The coating thickness is 100 μm-120 μm, the coating heating plate temperature is 25-80°C, and the scraper coating speed is 1-10 mm / s.

Citation Information

Patent Citations

  • Preparation method of lithium battery slurry

    CN109950462A

  • Method for improving stability of fuel cell slurry and corresponding electrode preparation method

    CN116826071A